Teaching-learning process of Situational Strategic Planning, in the training of medical professionals, during the period of Emergency Remote Teaching, in the year 2020: An experience report - Santana, Marcos Saulo Salviano; Braga, Joyce Pantoja; Miranda, Leticia Victoria Garcia; Cunha, Marcus Victor Balieiro; Silva, Ianka Aquino da; Geha, Yuri Fadi; Borges, Evelyn Teixeira; Barbosa, Anderson Veiga; Nascimento, Emerson André Negrão do; Pereira, Waltair Maria Martins (Seven Editora, 2023)
Acute Chagas Disease presents an alarming epidemiological situation in the Northern Region of Brazil, mainly due to the perennial neglect of the forms of prevention and prophylaxis by the social agents responsible for public health. The curricular content of the medical school of the Federal University of Pará, includes the Longitudinal Axis of Integral Care for the Health of the Individual, Family, and Community, the teaching of Situational Strategic Planning, in the exercise of the programming of actions of health promotion and prevention of diseases and diseases. This experience report aimed, in a moment of Emergency Remote Teaching, to identify the importance of teaching-learning of this type of planning for medical students. In the course of the experience in applying the simplification of the planning method proposed by Artmann (2000), there was great adherence from the students, as well as an approach to the formatting of an Intervention Project where the operations and actions thought were based on the goals of positive alteration of the indicators that declared the problem. the leading role in the literature review, for knowledge of acute Chagas disease and its epidemiological surveillance. As well as in the elaboration of the program, brought them closer and thought about humanized care and exercise proactivity, and let the sensitivity to the surface circumvent the local problems that can hinder the work focused on the well-being of a Community. DOI:https://doi.org/10.56238/devopinterscie-201